2016
DOI: 10.1007/s00439-016-1643-0
|View full text |Cite
|
Sign up to set email alerts
|

Blood group antigen loci demonstrate multivariate genetic associations with circulating cellular adhesion protein levels in the Multi-Ethnic Study of Atherosclerosis

Abstract: The cellular adhesion pathway is critical in the pathophysiology of atherosclerosis, and genetic factors contributing to regulation of circulating levels of related proteins may be relevant to risk prediction of cardiovascular disease. In contrast to conducting separate genome-wide protein quantitative trait loci (pQTL) mapping analyses of each individual protein, joint genetic association analyses of multiple quantitative traits can leverage cross-trait co-variation and identify simultaneous regulatory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…To date, most proteomics studies have been conducted using plasma samples from patients at higher risk for CVDs. [62][63][64][65][66] However, cell type-specific proteomic analyses using disease-relevant cells will be a valuable tool to dissect the origin of the proteome to accelerate the pathway to translation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most proteomics studies have been conducted using plasma samples from patients at higher risk for CVDs. [62][63][64][65][66] However, cell type-specific proteomic analyses using disease-relevant cells will be a valuable tool to dissect the origin of the proteome to accelerate the pathway to translation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, no functional study of LAMC2 has been carried out in the context of vascular biology and cardiovascular diseases; however, several studies showed its involvement in cancer [53][54][55][56][57] suggesting that LAMC2 plays a role in proliferation. To date, most proteomics studies have been conducted using plasma samples from patients at higher risk for cardiovascular diseases [58][59][60][61][62] . However, cell type-specific proteomic analyses using disease-relevant cells will be a valuable tool to dissect the origin of the proteome to accelerate the pathway to translation.…”
Section: Discussionmentioning
confidence: 99%